PENYELESAIAN SENGKETA TANAH SOKO PADA SUKU BENDANG KAMPAR RIAU DENGAN CORAK HUKUM ISLAM - Hengki Firmanda (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
The purpose of this study was to describe the ownership status of Soko land in the Indigenous People of the Bendang Tribe, Kampar, Riau; and explain the settlement of the transfer dispute over the ownership of Soko Land to the Indigenous People of the Bendang Tribe, Kampar, Riau. The existence of indigenous peoples will not be separated from their customary lands. The existence of indigenous peoples will be determined by ownership of their customary land. Indigenous people will not be called indigenous peoples without owning their customary land. This type of research is sociological legal research, namely research in the form of empirical studies to find theories about the process of occurrence and the process of working the law in society. The results of this study are, the status of ownership of Soko land in the indigenous people of the kampar tribe of the kampar district is attached to the community that has a maternal lineage. The transfer of ownership of soko land to the indigenous people of the dam tribe of Kampar District is the transfer of ownership of land between generations according to lineage and the transfer of land ownership to the settlement of land disputes.